Overexpression of TaNAC2D Displays Opposite Responses to Abiotic Stresses between Seedling and Mature Stage of Transgenic Arabidopsis - Huang, Quanjun; Wang, Yan (Frontiers in Plant Science, 2016)
Environmental stresses frequently affect plant growth and development, and many genes have been found to be induced by unfavorable environmental conditions. Here, we reported the biological functions of TaNAC2D, a stress-related NAC (NAM, ATAF, and CUC) gene from wheat. TaNAC2D showed transcriptional activator activity in yeast. TaNAC2D-GFP fusion protein was localized in the nucleus of wheat mesophyll protoplasts. TaNAC2D transcript abundance was significantly induced by NaCl, PEG6000, and abscisic acid (ABA) at seedling stage, and repressed by NaCl and PEG6000 at mature plant stage. When TaNAC2D was introduced into Arabidopsis, the 35-day-old soil-grown TaNAC2D-overexpression (TaNAC2D-OX) plants displayed slower stomatal closure, higher water loss rate, and more sensitivity to salt and drought stresses compared with WT plants. In contrast, TaNAC2D-OX seedlings, grown on 1/2 MS medium supplemented with different concentrations of NaCl, Mannitol, and MV, had enhanced tolerances to salt, osmotic and oxidative stresses during seed germination and post-germination periods. The opposite stress-responsive phenotypes of transgenic Arabidopsis were consistent with the expression patterns of TaNAC2D in wheat. Moreover, under high salinity and dehydration conditions, three marker genes, including NCED3, RD29A, and RD29B, were down-regulated in 35-d-old TaNAC2D-OX plants grown in soil and up-regulated in 14-d-old TaNAC2D-OX seedlings grown on 1/2 MS medium. Our results suggest that the change in growth stages and environmental conditions may regulate TaNAC2D’s function.